The Application of Augmented Reality Based Bingo Media in Teaching Arabic Vocabulary to Students at Rahma’ Islamic Junior High School - Mutiaturrahma; Susiawati, Wati; Fahri, Muhamad (Penerbit Minhaj Pustaka, 2026)
This study aims to examine the effectiveness of using Bingo media based on Augmented Reality (AR) in teaching Arabic vocabulary to eighth-grade students at Ruhama Islamic Junior High School. The research was motivated by students’ low mastery of vocabulary due to the dominance of traditional, less interactive teaching methods. The study employed a quantitative approach with a quasi-experimental design, involving two groups: an experimental group taught using AR-based Bingo and a control group taught using conventional methods. Data were collected through pre-tests and post-tests and analyzed using normality and homogeneity tests, the Mann–Whitney U test, and the N-Gain formula to measure learning improvement. The findings revealed a statistically significant difference between the two groups, with the experimental group achieving a higher post-test mean score (85.4) compared to the control group (36.1). The N-Gain average reached 81.57%, categorized as high effectiveness. These results demonstrate that AR-based Bingo is highly effective in enhancing students’ vocabulary acquisition, motivation, and active participation, while also promoting a more engaging and meaningful Arabic learning experience.